Analisis Dampak Penerapan Teori Manajemen Klasik Robert Owen dan Charles Babbage terhadap Efektivitas Pengelolaan Pendidikan di Madrasah Aliyah Muhammadiyah Rejang Lebong - Linda Ayu Syafitri; Deli Susanti; Wita Anggaini; Sutarto Sutarto (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the implementation of classical management theories proposed by Robert Owen and Charles Babbage in the educational management of Madrasah Aliyah Muhammadiyah Rejang Lebong and their impact on management effectiveness and educational quality. Employing a descriptive qualitative approach, data were collected through observation, documentation, and literature review. The findings reveal that classical management principles are implemented through systematic planning, structured division of labor, strengthened supervision, and enhanced motivation and welfare of teachers and staff. The application of efficiency and control principles contributes to improved discipline, professionalism, educational service quality, and graduate outcomes. Major challenges include limited funding, resistance to change, a lack of professional administrative personnel, and inadequate infrastructure, which are addressed through human resource development, technology utilization, stakeholder partnerships, and participatory leadership. The novelty of this study lies in the integrative application of Owen’s and Babbage’s classical management concepts within the contemporary Islamic educational context, an area that has received limited empirical attention. Theoretically, this research contributes to the development of Islamic educational management by offering a contextualized model of classical management theory adaptation. Practically, the findings provide implications for madrasah administrators in designing effective, efficient, and sustainable educational management practices aligned with modern educational demands